Automated inferior vena cava distensibility index for assessing fluid responsiveness in ventilated patients after cardiac surgery: a prospective pilot comparative study - Amr Salah Omar (17151028) (2025)
Objectives This study aimed to assess the accuracy of inferior vena cava distensibility index (IVC-DI) measurements, as well as the ability to track fluid responsiveness (FR) over time. Design Prospective, descriptive, single-center study Setting Single tertiary academic center. Participants Fifty consecutive after cardiac surgery. Interventions We compared 1) the automated echocardiographic method with 2) the stroke volume variation (SVV) technique and 3) the manual echocardiographic method. Measurements FR was measured simultaneously with all three methods in 50 patients after cardiac surgery. A second comparison was performed 90–180 min later. The outcomes assessed included the correlations between SVV with the automated IVC-DI and the manual IVC-DI, respectively before and after fluid challenge, as well as the accuracy of FR according to the automated and manual IVC-DI. FR was defined as an increase in cardiac output (CO) by more than 10% after receiving a fluid challenge. Results A total of 50 patients who underwent cardiac surgery were included (age 51 ± 8 years, male gender 86%). Before the fluid challenge, a negative correlation between automated and manual IVC-CI was observed (r= -0.141, p-value= 0.328) with a concordance rate of 98%, while the correlation became positive after fluid challenge (r= 0.172, p-value= 0.233) with a concordance rate of 98%. After fluid challenge, SVV correlation with automated IVC-DI and manual IVC-DI was positive, with the latter being statistically significant (r= 0.352, p-value= 0.012). FR predicted by automated IVC-DI was found to have a sensitivity 64% and specificity 49% of with ROC area under the curve of 0.55. Conclusions Among cardiac surgical patients, manual IVC-DI correlated significantly with SVV in assessing fluid responsiveness. However, the automated IVC-DI mode demonstrated less reliability. Other Information Published in: Journal of Cardiothoracic and Vascular Anesthesia License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1053/j.jvca.2025.08.023